KEPALA SEKOLAH SEBAGAI ADMINISTRATOR DAN SUPERVISOR - Muhammad Hasan Basari; Nadhira Safira; Naura Himayatul Fithiyyah; Amanda Septiana (JIP: Jurnal Ilmu Pendidikan, 2025)
The School Principal (Kepsek) holds a crucial dual role as Administrator (managing resources) and Supervisor (academic oversight), a duality often resulting in conflicting priorities that challenge school effectiveness. This study aims to analyze the integration strategy of this dual role and its correlation with the realization of effective Instructional Leadership. The method used is a Systematic Literature Review (SLR) of relevant scientific publications. The findings indicate that effective Kepsek successfully overcome time conflicts through Strategic Delegation of managerial tasks. The integration positions the administrative function as a foundation supporting the Kepsek to focus on academic supervision, coaching, and teacher professional development. The conclusion confirms that balancing the dual role is a fundamental prerequisite for improving overall teacher performance and educational quality.